Orchestra Conducting Skills: An Analytical Reading from the Perspective of Iraqi Symphony Orchestra Musicians (Al-Academy, 2025)
This study is based on the premise that musical leadership extends beyond the mere coordination and regulation of tempo; it encompasses the ability to inspire, to craft a compelling artistic vision, and to communicate effectively through both verbal and non-verbal means. These leadership skills range from technical-musical competencies to interpersonal and personal attributes. The research consists of four chapters: the first outlines the methodological framework, including the research problem, its significance, and objectives—specifically, an examination of orchestral conducting skills from the perspective of musicians in the Iraqi Symphony Orchestra—along with the research boundaries and the definitions of key terms. The second chapter presents the theoretical framework, offering a review of relevant literature and identifying key theoretical indicators. The third chapter details the research procedures, employing a descriptive-analytical approach; the research population and sample were selected through stratified sampling, and data were collected using a structured questionnaire designed to achieve the study’s objectives, which was distributed to members of the Iraqi Symphony Orchestra to gather their insights and perspectives on the topic. The fourth and final chapter presents the research findings and conclusions, followed by a series of recommendations and suggestions for further research, and concludes with a list of references.